Vocational Education and Training at higher levels of the EQF: Actions needed after 20 years of just talking - Daale, Hans [Verfasser] (My University, 2020)
"In the past twenty years, various attempts have been made to achieve harmonization of national education systems by 'Brussels' and thus at the European level, in order to make Europe more competitive. This has been done using broad-based plans in the Lisbon Strategy and ET2020, together with all kinds of sub-plans for the underlying education sectors. But only for higher education it has been possible to have far-reaching agreements, via the Bologna Process and the European Higher Education Area (EHEA). But the other sectors have certainly not been idle. For the Vocational Education and Training sector, consultations have been started with the European Commission since 2011 through a cluster of European VET organizations involved. But more will be needed in the coming years, partly because in the formal context VET runs up to and including level 4 of the European Qualifications Framework. The CHAIN5 platform was set up in 2013 to develop a sector with the qualifications at 5 and higher, in line with the approach in VET. This not only looks at a higher level of VET, but also at the Short Cycle HE, introduced in the EHEA in 2018. The essence of this article is to describe recent developments and to indicate that the discussions around level 5, in the broadest sense, should be high on the agendas of politicians and policymakers. So, it is a call for action, also with the consequences of COVID-19 in mind." (author's abstract; BIBB-Doku)
Keywords: I 2.2 Europa; S 2.3 Berufsbildungspolitik; EU-Bildungspolitik; Berufsbildungspolitik; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Höhere Berufsbildung